The Association between Deoxyribonucleic Acid Hypermethylation in Intron VII and Human Leukocyte Antigen-C∗07 Expression in Patients with Endometriosis - Wenrong Zhao; Lei Lei; Rui Chen; Yanmin Zhang; Linlin Chang; Jingxin Cheng (International Journal of Clinical Practice)
Objective. Endometriosis, which is a common disease affecting approximately 10% of women of reproductive age, usually causes dysmenorrhea and infertility, thus seriously harming the patients’ physical and mental health. However, there is a mean delay of 6.7 years between the onset of the symptoms and the surgical diagnosis of endometriosis. There is an increasing amount of evidence that suggests that epigenetic aberrations, including deoxyribonucleic acid (DNA) methylation, play a definite role in the pathogenesis of endometriosis. This study aimed to explore the noninvasive or minimally invasive biomarkers of this disease. Materials and Methods. Six patients with surgically confirmed ovarian endometriosis and six patients who received IUD implantation for contraception without endometriosis were recruited in the East Hospital of Tongji University in 2018. The genome methylation profiling of the eutopic and ectopic endometrium of ovarian endometriosis patients and normal endometrial specimens from healthy women was determined using a methylation microarray test. The test screened methylation-differentiated 5′–C–phosphate–G–3′ (CpG) sites and then located the target genes affected by these sites following sequence alignment. Then, an additional 22 patients and 26 healthy controls were enrolled to further verify the difference in the selected genes between endometriosis patients and healthy women. The differential DNA methylation of the selected genes was validated via direct bisulfite sequencing and analysis of their messenger ribonucleic acid (mRNA) levels using quantitative reverse transcription polymerase chain reaction (qRT-PCR). Results. Fifteen differentially methylated CpG sites were found among the patients and healthy women, and five CpG sites were mapped to the introns of the human leukocyte antigen-C (HLA-C) gene; these were highly polymorphic between different HLA-C alleles and were HLA-C∗07 specific. The results indicated that the HLA-C∗07 carrier patients exhibited significantly higher DNA methylation levels at the intron VII of HLA-C compared to the HLA-C∗07 carrier healthy controls. High HLA-C∗07 mRNA levels were also observed using qRT-PCR with HLA-C∗07-specific primers, which indicated that the hypermethylation of CpG in intron VII might suppress a silencer that regulates HLA-C∗07 expressions. Conclusion. Deoxyribonucleic acid hypermethylation in the intron VII of the HLA-C∗07 gene appears to regulate the expression of HLA-C∗07. The aberrant DNA methylation in this region was positively correlated with the occurrence of endometriosis.